Prediction of molecular weight distributions in polymers using probability generating functions - Sarmoria, Claudia (2012)
We review the work of our group in the area of mathematical modelling of polymerisation reactors and processes, with emphasis in the prediction of molecular weight distributions using probability generating functions (pgfs). We apply the method to a polymerisation example for which the analytic solution is known, and show that its predictions are very accurate. We also compare the performance of the method to that of the straightforward integration of the mass balances of the reacting system, showing that the pgf method results in very fast calculations. We end by discussing ongoing and future applications of the method.